Multiyear ice replenishment in the Canadian Arctic Archipelago: 1997–2013. Issue 3 (14th March 2015) - Howell, Stephen E. L.; Derksen, Chris; Pizzolato, Larissa; Brady, Michael
Abstract In the Canadian Arctic Archipelago (CAA), multiyear ice (MYI) replenishment from first‐year ice aging (CAAMYI‐Oct‐1) and Arctic Ocean MYI exchange (CAAMYI‐exchange) contribute to the CAA's relatively heavy sea ice conditions at the end of the summer melt season. We estimate these components using RADARSAT and the Canadian Ice Service Digital Archive and explore processes responsible for interannual variability from 1997 to 2013. CAAMYI‐Oct‐1 (52 ± 36 × 103 km2) provides a larger contribution than CAAMYI‐exchange (13 ± 11 × 103 km2). CAAMYI‐Oct‐1 represents ∼10% of the amount that occurs in the Arctic Ocean. CAAMYI‐exchange represents ∼50% of Nares Strait MYI export to Baffin Bay and ∼12% of Fram Strait MYI export to the Greenland Sea. CAAMYI‐Oct‐1 exhibits dependence on warmer (cooler) summers that increase (decrease) melt evident from strong relationships to surface air temperature (SAT), albedo and total absorbed solar radiation (Qtotal). CAAMYI‐exchange is influenced by summer sea level pressure (SLP) anomalies over the Beaufort Sea and Canadian Basin which shifts the primary source of CAAMYI‐exchange between less obstructed M'Clure Strait (low SLP anomalies) and the more obstructed Queen Elizabeth Islands (high SLP anomalies). Over the 17‐record, appreciable replenishment occurred for most years from 1997 to 2004, reduced replenishment from 2005 to 2012, and large replenishment in 2013. The reduced replenishment period was associated with positive SAT, negative albedo, and positive Qtotal anomalies that facilitated more melt and less CAAMYI‐Oct‐1, together with high SLP anomalies that facilitated less CAAMYI‐exchange. Large replenishment in 2013 was primarily from CAAMYI‐Oct‐1 attributed to strongly negative SAT and Qtotal anomalies and strongly positive albedo that impeded melt.